FINANCIAL MANAGEMENT FOR ORPHANAGE ADMINISTRATION - Alistraja Dison Silalahi; Debbi Chyntia Ovami; Rizqy Fadhlina Putri; Noh Aisyah Mohd Ali; Rahmad Gunawan; Muhammad Dimas Alfahri (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This Community Partnership Empowerment (PKM) offers community activity programs as a solution to existing problems in the form of socialization and training to all orphanage administrators in making simple financial management and financial statements of non-profit organizations. The implementation methods carried out in this activity program are planning, implementation, and sustaibability. This activity involves university students from various fields as a form of collaboration. The participating students consisted of 2 students from faculty of economics and business UMN Al Washliyah The students are given the task of assisting partners in mentoring the management of the Al-Washliyah Orphanage. The result of this community shows that the interest of Al-Washliyah Orphanage service participants to practice this service activity has been successful. About 70% of owners and employees attend and feel happy to take part in this training because it can add insight into risk management. Partners greatly contribute to the smooth running of community service activities.